We are in this together — Aren't we? Congruence of common dyadic coping and psychological distress of couples facing breast cancer. Issue 12 (22nd October 2019) - Meier, Fabienne; Cairo Notari, Sarah; Bodenmann, Guy; Revenson, Tracey A.; Favez, Nicolas
Abstract: Objectives: Breast cancer (BC) can be understood as a we‐disease, which affects a couple as a unit and requires coping as a unit (eg, common dyadic coping, CDC). However, partners can be incongruent in their perceptions of CDC, for example, because of misunderstandings and lack of mutuality or conflict, which may likely be associated with greater distress. Thus, this paper examines the effect of CDC congruence on individual psychological distress in cancer patients and their partners. Methods: Seventy mixed‐sex couples in which the woman had nonmetastatic BC completed self‐report questionnaires at 2 weeks, 3 months, and 1 year after cancer surgery. CDC congruence measured the difference between patients' and partners' CDC perceptions while controlling for CDC itself. Results: Multilevel modeling showed negative associations between couples' CDC and psychological distress. Beyond this effect, female patients' psychological distress was associated with CDC congruence with an interaction showing that psychological distress was greater when couples were congruent with low rather than a high CDC. Conclusion: Less congruence was associated with greater psychological distress in BC patients but not their male partners — especially if the couple reported low CDC. Health professionals should identify and address diverging perceptions, so that additional distress can be minimized for BC patients.